Effect of moisture stress and growth regulating compounds on water use and yield of transplanted rice - Ajaykumar, R; krishnasamy, S Murali; Kumaresan, P; Navinkumar, C (ORYZA-An International Journal of Rice, 2023)
A Field research was carried out at the Wetland Farm, Department of Farm Management, Tamil Nadu Agricultural University, Coimbatore during the Rabi and Summer seasons of 2017 and 2018, to examine the effects of moisture stress and growth-regulating compounds on nutrient uptake, water use efficiency, water productivity, and yield of transplanted puddled rice. Three replications of split plot designs were used for field experiment. The treatments includes foliar applications of growth-regulating compounds, such as chlormequat chloride at 200 ppm, mepiquat chloride at 200 ppm brassinolide at 0.1 ppm , Pink Pigmented Facultative Methylotrophs (PPFM 1%) and Control (No spray) at different growth stages, such as panicle initiation stage, flowering stage, and both panicle initiation and flowering stage. The moisture stress free control is implemented by irrigating the field with 5 cm of irrigation each day after the disappearance of previously ponded water. Treatment combination of moisture stress at panicle initiation stage along with 0.1 ppm brassinolide had recorded to increased WUE of 7.09, 6.68 kg ha-mm-1 and water productivity of 0.71 and 0.67 kg m-3, respectively during Rabi and summer season. Treatment combination of moisture stress at both panicle initiation and flowering stages along with PPFM registered lower WUE with 6.19 and 5.78 kg ha-mm-1 and lower water productivity with 0.62 and 0.58 kg m-3, during both the seasons. it could be concluded that, foliar application of 0.1 ppm brassinolide for mitigating the moisture stress at panicle initiation stage alone and one per cent PPFM spray when crop suffered moisture stress at flowering phase were effective in mitigating the moisture stress in attaining the maximum crop yields.